2015
DOI: 10.3389/fmicb.2015.00100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of coupling drug transport reactions located in two different membranes

Abstract: Gram- negative bacteria utilize a diverse array of multidrug transporters to pump toxic compounds out of the cell. Some transporters, together with periplasmic membrane fusion proteins (MFPs) and outer membrane channels, assemble trans-envelope complexes that expel multiple antibiotics across outer membranes of Gram-negative bacteria and into the external medium. Others further potentiate this efflux by pumping drugs across the inner membrane into the periplasm. Together these transporters create a powerful ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 99 publications
(178 reference statements)
2
50
0
Order By: Relevance
“…They claimed that the dimer is the entity that binds to TolC and that AcrA functions as a dimer (41). Those reports supported a 1:2:1 stoichiometry.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They claimed that the dimer is the entity that binds to TolC and that AcrA functions as a dimer (41). Those reports supported a 1:2:1 stoichiometry.…”
Section: Discussionsupporting
confidence: 59%
“…These experiments indicated that the ␣-hairpins of AcrA interact with TolC and that the other three domains of AcrA interact with the DN and PN2 subdomains of AcrB. On the other hand, surface plasmon resonance studies indicated that AcrA exists as a dimer (39,40) and that the dimer is the entity that binds to TolC, suggesting 1:2:1 stoichiometry in vitro (41). Recently, 3:6:3 models were also proposed on the basis of electron microscopy (EM) images of the AcrAB-TolC complex.…”
mentioning
confidence: 99%
“…The lipoyl, ␤-barrel, and membrane-proximal domains are made primarily of ␤-strands. The latter domains stabilize interactions with the transporter protein (6,9).…”
mentioning
confidence: 99%
“…In the resting state, the aperture of the OMF remains in a closed state and only upon functional interactions with the inner membrane components of the tripartite complex does the OMF transition into an open state, allowing efflux of substrates into the extracellular milieu (4)(5)(6)(7)(8) (Fig. 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation